Pregnancy, Genetic Risk and Congenital Heart Disease - Jost, Christine H. Attenhofer; Connolly, Heidi M. (SA Heart Journal, 2017)
An increasing number of women with congenital heart disease (CHD) are reaching childbearing age and are considering pregnancy. Pregnancy is tolerated well in most of these women with unoperated, or repaired cardiac lesions; however, the risk is increased considerably in certain situations such as pulmonary hypertension, severe valvular stenosis, pulmonary atresia, mechanical prosthetic valves, with Fontan type circulation, in Marfan syndrome and other aortopathy. Counseling prior to pregnancy in CHD also involves discussion of genetic testing, possibility of transmission to the child, management during pregnancy including preimplantation genetic testing, and recommendations regarding fetal echocardiography. All medications including anticoagulation options if needed should be carefully reviewed prior to pregnancy due to maternal and fetal risks. If needed, cardiac surgery or balloon valvuloplasty can be carried out with an increased risk to mother and fetus. Overall, pregnancy in CHD is feasible in most patients with good maternal and fetal outcome. High risk pregnancy patients with CHD have to be counseled by a multidisciplinary team including cardiologists, obstetricians and anesthesiologists at a tertiary care center.